Sanksi Pidana Terhadap Pelaku Penjambretan Mengakibatkan Matinya Korban - I Putu Bayu Suryadinatha; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
Increasing crime mugging, crime that commits crime by confiscating valuables. Based on this research, the writer raises the formulation the problem: 1. How regulation mugging criminal sanctions, 2. How imposition criminal sanctions for the perpetrator that results as result mugging. This type research uses the normative method, with an invited-invited, conceptual, case approach. regulation mugging criminal is articles 362-367 of Criminal Code concerning robbery, where mugging regulated in Criminal Code, so crime mugging refers to article 365 paragraph (3) criminal act robbery with violence. Perpetrators mugging which result in death may be subject to Article 365 paragraph (3) with a maximum penalty 15 years in prison. regulation mugging crime based on Articles 362-367 Criminal Code because mugging included in category violent crime which deals with the elements article 365 paragraph (3) robbery with violence. Mugging subject to imprisonment and imprisonment for the mugging subject to a maximum imprisonment of 15 years. Mugging is regulated in article 362 if not with violence and 365 paragraph (3) if it is done with violence. For law enforcers, it is better if law enforcers use the Man In The Street model in providing protection to the community.